Komposisi vegetasi pada Daerah Aliran Sungai Pangasi Kawasan Cagar Alam Pangi Binangga Kabupaten Parigi Moutong - Pramayanti, Diah Natasya Arif; Naharuddin, Naharuddin; Rosyid, Abdul; Purnama, Rizky; Maiwa, Arman; Hulu, Amati Eltriman (Fakultas Kehutanan Universitas Mulawarman, 2024)
This research aims to determine the types of plants and the Important Value Index in the Pangasi River Watershed (DAS) in the Pangi Binangga Nature Reserve. The method used in collecting data is the plot method or checkered path method with four growth levels, namely seedlings (20 m × 20 m), saplings (10 m × 10 m), poles (5 m × 5 m) and trees (2 m × 2 m). Data analysis used the Importance Value Index (INP), a method commonly used in ecological studies. INP analysis includes several parameters, namely relative density, relative frequency, and relative dominance. The results of field identification found 532 individuals with 19 species. Vegetation Analysis Results: Important Value Index at tree level is dominated by Bayur (Pterospermum spp), the pillar level is dominated by Ebony (Diospyros celebica bakh), at the stake level dominated by Pangi/Kepayang (Pangium to success) and at the pillar level dominated by Nyatoh (Palaquium obtusifolium). Results of INP calculations at tree, pole, sapling and seedling levels. In general, of the four growth levels, Nyatoh (Palaquium obtusifolium) is the most dominant plant in the Pangasi River Basin.